2013
DOI: 10.1536/ihj.54.23
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Transforming Growth Factor <I>&beta;</I>-1 Level in Japanese Patients With Marfan Syndrome

Abstract: SummaryMarfan syndrome (MFS) is an inherited connective tissue disorder mainly caused by the fi brillin-1 mutation. Deficient fi brillin-1 is thought to result in the failed sequestration of transforming growth factor β (TGFβ) and subsequent activation of the TGFβ signaling pathway, suggesting that the circulating TGFβ level may be elevated in MFS, although its accurate measurement is complex due to ex vivo release from platelet stores upon platelet activation. We measured the plasma TGFβ1 levels of 32 Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Indeed, mutations in the FBN1 gene, present in most patients with Marfan syndrome, lead to deregulation of TGF-β bioavailability and to a consequent derangement in TGF-β autocrine and paracrine molecular signaling [24]. Evidence has also been provided that the circulating levels of TGF-β are increased in Marfan patients, although ethnic differences and technical issues may confound results [25][26][27]. Two studies have also reported higher levels of circulating TGF-β in patients with larger aortic diameter, faster aortic growth rate, previous aortic surgery and acute aortic events during follow-up, including Stanford type B AD and necessity of aortic replacement [26,28].…”
Section: Tgf-βmentioning
confidence: 99%
“…Indeed, mutations in the FBN1 gene, present in most patients with Marfan syndrome, lead to deregulation of TGF-β bioavailability and to a consequent derangement in TGF-β autocrine and paracrine molecular signaling [24]. Evidence has also been provided that the circulating levels of TGF-β are increased in Marfan patients, although ethnic differences and technical issues may confound results [25][26][27]. Two studies have also reported higher levels of circulating TGF-β in patients with larger aortic diameter, faster aortic growth rate, previous aortic surgery and acute aortic events during follow-up, including Stanford type B AD and necessity of aortic replacement [26,28].…”
Section: Tgf-βmentioning
confidence: 99%
“…Circulating TGFβ1 is not diagnostic and therapeutic marker for Japanese patients with Marfan syndrome, although ndings don't eliminate the possible association of TGFß with the pathogenesis of Marfan syndrome, what we have not been able to con rm nor exclude, due to technical limits in genetic examinations 4 .…”
mentioning
confidence: 63%
“…24) Chaudhry, et al demonstrated that mutation of fibrillin-1 altered intercellular communication and significantly increased TGF-β protein levels in the extracellular space. 25) TGF-β is a paracrine regulatory molecule involved in several processes.…”
Section: Tgf-β Is a Common Critical Factor In Mfs Cardiovascular Dismentioning
confidence: 99%